Breathing Patterns During Job-Related Tasks for Home Healthcare Workers Influencing Aerosol Exposure. - Bellacov, Ryan L.; Davis, Kermit G.; Wang, Jun; Kotowski, Susan (Home Health Care Management & Practice, 2026)
Home healthcare workers (HHCWs) experience a higher incidence of hazardous bioaerosol exposures compared to workers in many other occupational sectors. This study explores how the working postures of HHCWs influence lung volume, which would relate to aerosol exposure assessments of these workers. A controlled laboratory study investigating 8 job tasks for 20 HHCWs including static trunk postures (upright, 30°, 60°, and 90°) and dynamic postures (patient lift and equipment lift). The dependent variables were oxygen consumption, tidal volume, and respiration rate. The HHCWs job tasks of patient handling and equipment lift had double the respiration rate compared to the static posture tasks (35 bpm vs 15 bpm). In the static job tasks, standing upright had a tidal volume of 12 L, with forward-leaning postures reduced to 8 L. When comparing amplitude abdominal expansion, forward-leaning postures gave the most differences, from 13.7 w to the lowest 2.2 w. The results of the analysis of variance (ANOVA) and post-hoc Tukey tests indicate that almost all tested postures have a significant impact on lung spirometry (p <.001; 15 of 20 postures). The study findings indicate that lung spirometry was altered by posture and activity level, which likely changes the aerosol exposures. HHCWs commonly perform patient handling tasks, not only putting themselves at risk for musculoskeletal injuries but also increasing bioaerosol risk. Failure to account for body postures may result in worker exposure being misestimated. This study demonstrated that posture and activity level influence aerosol exposure and needs be considered when investigating multiple exposures.